Attractiveness of Education in Russia: Achievements and Challenges - V. L. Petrov; V. F. Pugach (Moscow Polytechnic University, 2020)
The paper considers an approach to assess the attractiveness of education in post-Soviet Russia. The authors present the findings of an analysis of the dynamics of population's attitude to education in terms of verbal behavior indicators, such as opinions about purposes of saving and spending money on education depending on per capita income. The paper shows the evolution of education place in personal consumption expenditures and in payments for personal services. It also presents the results of comparative study on education characteristics of the population in Russia and in some major economies. A conclusion is made about high attractiveness of education in our country as well as about an obvious trend to its decline in the XXI century.